PENGARUH LATIHAN BEREDAR DENGAN BOLA TERHADAP KETEPATAN MENENDANG BOLA PADA PEMAIN U-17 SSB SATRIA ZAHRA PEKANBARU - Putra, Rahmat Septia Putra Septia; ', Slamet; ', Yuherdi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract This study was conducted to determine whether there was an effect of outstanding practice with the ball for the accuracy kicking the ball in a game of football that at the time of shooting the ball to get maximum results. The shape of this research is the experimental treatment (Experimental), with a population of players U-17 SSB Satria Zahra Pekanbaru, the data in this study is the entire population of 12 people. The instruments used in this research is test fired the ball into the goal, which aims to measure the accuracy of shooting the ball. After that, the data is processed with statistics, to test the normality of the test at a significant level 0,05α lilifors. The hypothesis is the effect of exercise Circulating With Soccer Ball Kicking Against The accuracy. Based on t test analysis produces Thitung of 1.657 and 1.796 for Ttabel, meaning Thitung <Ttabel. Thus, there is no Influence of Exercise Circulating With Ball Kicking Ball Against Accuracy In the U-17 Player of the SSB Satria Zahra Pekanbaru. Keywords: Circulated with the Ball, Kicking a Ball Accuracy